GE_GERICHTE A/3585/2024 vom 4. April 2025 - GE Cour de justice (2025)
ÉCHANGE DE PERMIS;PERMIS DE CONDUIRE;SAISIE DE PERMIS;COURSE DE CONTRÔLE | LCR.10.al2; LCR.22.al1; LCR.14.al1; OAC.42.al1; OAC.45; OAC.23